Źródła i konsekwencje wzrostu elastyczności rynku pracy - Łucjan, Izabela (Annales. Etyka w Życiu Gospodarczym, 2016)
The transformation of the modern world of work towards the information society, knowledge society, have a rapid course. These transformations take on a global character, and the most of their consequences are negative. One of them is to base the employment process on the flexible solutions. Nowadays, neither the high level of education, nor the high competences are not enough to give confidence in finding employment. The contemporary labour market is characterised by unstableness, ‘elusiveness’ and, above all, flexibility. The challenge has become a flexible company, which employs only flexible workers within the framework of flexible forms of employment. Despite its universality, the concept of flexibility still remains inconsistent and vaguely defined.